2007
DOI: 10.1007/s10886-007-9308-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Memory of Mountain Birches: Effects of Phenolics on Performance of the Autumnal Moth Depend on Herbivory History of Trees

Abstract: Plants have been suggested to have an immunological memory comparable to animals. The evidence for this, however, is scarce. In our study with the mountain birchEpirrita autumnata system, we demonstrated that birches exposed as long as 5 yr to feeding of E. autumnata larvae (delayed induced resistance, DIR), responded more strongly to a new challenge than trees without an herbivory history. Pupal weights remained lower, and the duration of the larval period was prolonged in the DIR trees, although immunity, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…Studies in insects testing sexual dimorphism in immune defense have resulted in mixed findings (for example, CordobaAguilar et al, 2006, Rantala andRoff, 2007). It has been found that there is sex difference in response to genetic (Rantala and Roff, 2007) and nutritional stress (McKean and Nunney, 2005;Ruuhola et al, 2007) that may cause between population and species variation in sex difference in immunity. In the present case, encapsulation ability was highest in females and the gender difference showed a modest or no change with temperature.…”
Section: Sexual Dimorphism In Immune and Life-history Traitsmentioning
confidence: 99%
“…Studies in insects testing sexual dimorphism in immune defense have resulted in mixed findings (for example, CordobaAguilar et al, 2006, Rantala andRoff, 2007). It has been found that there is sex difference in response to genetic (Rantala and Roff, 2007) and nutritional stress (McKean and Nunney, 2005;Ruuhola et al, 2007) that may cause between population and species variation in sex difference in immunity. In the present case, encapsulation ability was highest in females and the gender difference showed a modest or no change with temperature.…”
Section: Sexual Dimorphism In Immune and Life-history Traitsmentioning
confidence: 99%
“…Immunological memory of mountain birch after herbivory by autumnal moth is discussed by Ruuhola et al (2007). They found out that delayed induced resistance lasted as long as five years.…”
Section: Possible Reason For High Sesquiterpene Emissionmentioning
confidence: 99%
“…Mechanical damage of leaf tissue is known to induce an immediately enhanced production and emission of volatiles (Juuti et al, 1990). However, it has also been suggested that an immunological memory effect of herbivore attacks, potentially affecting the composition of the emitted VOC mixture, may persist for several years after the actual defoliation event (Ruuhola et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies conducted on relationships between individual phenolic compounds and herbivory have given contrasting results Ruuhola et al, 2007). A plant's suitability for herbivores also has been connected to plant oxidases, such as polyphenoloxidases (PPOs) and peroxidases (PODs) (Felton et al, 1989;Appel, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Methods for extraction, analysis, and identification of phenolic compounds are described in Salminen et al (1999Salminen et al ( , 2001. Enzyme activities of the birch leaves were analyzed as in Ruuhola and Yang (2006) and Ruuhola et al (2007). Enzyme activities were measured in triplicate.…”
Section: Methodsmentioning
confidence: 99%